Fast Popularity Value Calculation of Virtual Cryptocurrency Trading Stage Based on Machine Learning - Zhu, Tong; Liao, Chenyang; Zhou, Ziyang; Li, Xinyu; Zhang, Qingfu (Frontiers in Physics, 2022)
This paper proposes a new definition method of currency, which further divides the current hot digital currency according to its legitimacy, encryption, centralization and other characteristics. Among these, we are mainly interested in virtual cryptocurrencies.Virtual cryptocurrency is one of the application directions of blockchain technology. Its essence is a distributed shared ledger database, which generally has the characteristics of decentralization and non-tampering.The technologies supporting the practical application of virtual cryptocurrencies involve multiple scientific and technological fields such as mathematical algorithms, cryptography, Internet communication and computer software.Since the launch of the first virtual cryptocurrency bitcoin in 2009, it has developed rapidly worldwide. As of August 1, 2021, more than 11,570 virtual cryptocurrencies have been publicly issued and traded globally, with a total value of over 1.68 trillion.This paper proposes the virtual cryptocurrency trading popularity value system as a standardized index for quantitative analysis of virtual cryptocurrency trading, and the virtual cryptocurrency trading index system as a barometer of the virtual cryptocurrency trading market. It has contributed schemes to the analysis of the market rules of virtual cryptocurrency transactions and the realization and early warning of abnormal virtual cryptocurrency transactions, which are the two main hot research directions of virtual cryptocurrency.To be specific, the popularity value of virtual cryptocurrency transactions provides parameters for analyzing individual virtual cryptocurrencies, and the popularity index of virtual cryptocurrency transactions provides parameters for analyzing the virtual cryptocurrency trading market, so as to prevent major risks of virtual cryptocurrency transactions.